Vitamin D deficiency in pediatric critical illness() - Hebbar, Kiran B. (J Clin Transl Endocrinol, 2014)
INTRODUCTION: The potential role for vitamin D in infection has been well described in adults. The objective of our study was to determine the prevalence of vitamin D insufficiency and to evaluate the relationship between vitamin D status and markers of innate immunity and infection in critically ill children. HYPOTHESIS: Vitamin D deficiency is highly prevalent in children with critical illness and correlates with the severity of illness and dysfunction in innate immunity. METHODS: We performed a prospective clinical observational study with both case and control groups in the pediatric intensive care unit (PICU). Vitamin D status was defined as vitamin D sufficient (25-hydroxyvitamin D (25(OH)D ≥ 20 ng/mL), vitamin D insufficient (25(OH)D 10–20 ng/mL), and vitamin D deficient (25(OH)D <10 ng/mL). Vitamin D status, severity of illness scores, and cathelicidin, and other clinical data were collected. RESULTS: Sixty-one PICU patients and 46 control patients were enrolled. Over 60% of the PICU cases were found to be vitamin D insufficient while less than 1/3 of the controls were insufficient (p < 0.0001). No significant correlation was seen between plasma 25(OH)D and any severity of illness scores. Cases with asthma had a significantly lower median level 25(OH)D (16.9 ng/mL) than cases without asthma (18.7 ng/mL). Over 50% of patients hospitalized during the fall and winter were considered vitamin D deficient or insufficient whereas in the sunnier seasons (spring and summer) the prevalence of vitamin D deficiency/insufficiency decreased to about 30% (p = 0.003). CONCLUSIONS: Vitamin D deficiency is common in the pediatric critical care population. Significant seasonal differences were noted even in the critically ill. The role of vitamin D in certain diseases like asthma in critically ill children merit further study.